2021
DOI: 10.1016/j.radonc.2020.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Inter-fraction motion robustness and organ sparing potential of proton therapy for cervical cancer

Abstract: Large-field photon radiotherapy is current standard in the treatment of cervical cancer patients. However, with the increasing availability of Pencil Beam Scanning Proton Therapy (PBS-PT) and robust treatment planning techniques, protons may have significant advantages for cervical cancer patients in the reduction of toxicity. In this study, PBS-PT and photon Volumetric Modulated Arc Therapy (VMAT) were compared, examining target coverage and organ at risk (OAR) dose, taking inter-and intrafraction motion into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Our results are in line with the ones of Gort et al [17] which showed by analyzing repeat CT scans, that ITV-based treatment plans with PBS-PT and photon therapy were equally robust to interfractional motion. However, it is interesting to note that their worst D98% dose degradation of the uterus was of less than 30%, while in our study fractions with dose degradation greater than 80% was observed in one patient.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in line with the ones of Gort et al [17] which showed by analyzing repeat CT scans, that ITV-based treatment plans with PBS-PT and photon therapy were equally robust to interfractional motion. However, it is interesting to note that their worst D98% dose degradation of the uterus was of less than 30%, while in our study fractions with dose degradation greater than 80% was observed in one patient.…”
Section: Discussionsupporting
confidence: 92%
“…Berger et al [6] showed that gas cavities and outline variations had minor impact on target and OARs doses. In addition, the study by Gort et al [17] indicated that, with all sources of uncertainties considered, robustly optimized PBS-PT was equally robust against inter-and intrafraction variability compared to photon therapy and provides better OARs sparing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior fields are often used in pelvic proton therapy, to reduce impact from changing bowel gas/fillings, weight and other variable conditions [13,18]. This can result in slightly higher dose to the parts of the sacral bone close to the CTV.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial physical characteristics of proton therapy and its ability to achieve satisfactory target dose distributions using only a few beams enables BMS [22,23]. Gort et al and Dinges et al showed significantly better BMS for proton therapy when compared to photon therapy [22,24]. However, knowledge on the spatial location of bone marrow sparing and the required degree of sparing is essential for the development of BMS-radiotherapy techniques [25].…”
Section: Introductionmentioning
confidence: 99%